Descriptor extraction on inherent creep strength of carbon steel by exhaustive search. Issue 1 (1st January 2021) - Sakurai, Junya; Demura, Masahiko; Mototake, Yoh-ichi; Okada, Masato; Yamazaki, Masayoshi; Inoue, Junya
ABSTRACT: The alloying elements that control the creep rupture life of low carbon steel in the region of inherent creep strength were investigated by a data-driven model selection method. The experimental data published in NRIM Creep Data Sheet No. 7B was used. A model in which the Larson–Miller parameter is expressed as a linear sum of the logarithmic stress and the chemical composition of alloying elements was proposed on the basis of the analysis of the experimental data. There were 1023 ( = 2 10 − 1 ) candidate models containing one or more of the 10 alloying elements, and they were compared using two model selection methods: 10-fold cross validation (CV) and posterior probability based on Bayesian inference. The 10-fold CV suggested that Mo must be included in the model to improve the predictivity of the unknown data. A comparison among the Bayesian posterior probabilities of the candidate models showed that the Mo-only model has a predominantly high posterior probability of 79.76% compared with the other models. Furthermore, other element terms that co-occur with Mo evenly appeared in the top list after the Mo-only model, indicating that only Mo is crucial for increasing the posterior probability. From these results, it is concluded that the Mo-only model is the most appropriate as a data generation model. The selected Mo-only model was confirmed to have high predictivity of the creep life. Graphical abstract: uf0001